Strategi Dan Metode Pebelajaran Akidah Akhlak - Hasan, Zubaidi; Zubairi, Zubairi (STAI Asy-Syukriyyah, 2023)
Strategies and methods in learning is a process of teaching and learning activities to achieve learning goals. From the learning process there will be reciprocal activities between teachers and students to achieve better goals. The learning process is a process in which there are teacher-student interaction activities and reciprocal communication that take place in educative situations to achieve learning objectives. Approach In this study with the literature, which analyzes strategies in the learning process between teachers and students, where the interactions between the two are two components that cannot be separated. There is mutually supportive interaction so that student learning outcomes can be achieved optimally. The strategies and methods carried out by a teacher of aqidah akhlaq can shape the Islamic character of students.